Toxic epidermal necrolysis as presenting manifestation of cutaneous lupus erythematosus in a 17-year-old girl. - Cardona-Salazar, M.; Mora-Talero, L.C.; Trujillo Hernández, M.; Lozano Rivera, I.M.; Reina Ávila, M.F.; Díaz Maldonado, A.S. (European Journal of Pediatric Dermatology, 2023)
Toxic epidermal necrolysis is a rare cutaneous manifestation of systemic lupus erythematosus with a mortality rate of up to 28% in the pediatric population. Here was reported the case of a 17-year-old girl with no relevant family or personal history who suddenly presented extensive burn-like lesions prevalently on the trunk. The diagnoses of toxic epidermal necrolysis and multisystem inflammatory syndrome of the child associated with SARS CoV-2 infection were considered. However, laboratory tests led to the final diagnosis of cutaneous lupus erythematosus. The patient was treated with intravenous immunoglobulins and once the symptoms resolved she was discharged with azathioprine, prednisolone and chloroquine.